High resolution core level spectroscopy of hydrogen-terminated (1 0 0) diamond. (14th June 2016) - Schenk, A K; Rietwyk, K J; Tadich, A; Stacey, A; Ley, L; Pakes, C I
Abstract: Synchrotron-based photoelectron spectroscopy experiments are presented that address a long standing inconsistency in the treatment of the C1s core level of hydrogen terminated (1 0 0) diamond. Through a comparison of surface and bulk sensitive measurements we show that there is a surface related core level component to lower binding energy of the bulk diamond component; this component has a chemical shift of − 0.16 ± 0.05 eV which has been attributed to carbon atoms which are part of the hydrogen termination. Additionally, our results indicate that the asymmetry of the hydrogen terminated (1 0 0) diamond C1s core level is an intrinsic aspect of the bulk diamond peak which we have attributed to sub-surface carbon layers.